Nigella sativa L., Supplementary Plant with Anticholinesterase Effect for Cognition Problems: A Kinetic Study - Ansari, Mehdi; Mandegary, Ali; Mosalanejhad, Niloofar; Asadi, Amir; Sharififar, Fariba (Current Aging Science, 2020)
Background: The average lifespan and the aging population are rising worldwide. So Neurodegenerative Disease (ND) will be one of the most common challenges associated with this population and would be more prevalent in future. The use of Acetylcholinesterase (AChE) inhibitors is one of the most important strategies for memory impairment. Medicinal plants are the most known natural source for accessing the new therapeutic agents. Objective: In this work, we aimed to study in vitro anticholinesterase effect of different concentrations (10, 100, 250, 500, 750 and 1000 μg/ml) of total extract of N. sativa (NTE) and its separated fractions and to study the kinetic of AChE enzyme in the presence of two concentrations of NTE (10 and 100 μg/ml). Methods: Maceration method was used for NTE preparation and different fractions of Petroleum Ether (PTE), Chloroform (CHF) and Methanol (MF). NTE, fractions and the main component of the plant, Thymoquinone (TQ), were assayed for AChE inhibition, using Ellman’s method. Kinetic study of the AChE enzyme was studied in the presence of NTE at 10 and 100 μg/ml using Linweaver- Burk plot too. Results: NTE and all the separated fractions inhibited AChE enzyme in a concentration-dependent manner. The greatest inhibition was shown by CHF and PEF fractions (86.97% and 79.99% at 1000 μg/ml, respectively). With less intensity, NTE, TQ and MF exhibited 76.32%, 68.98 % and 48.39% enzyme inhibition at 1000μg/ml, respectively. The least IC50 value was due to CHF fraction in AChE inhibition (98.28 ± 6.74 μg/ml). Kinetic profile exhibited the mixed mode of AChE inhibition by NTE. This indicates that a particular substance could not be responsible for AChE inhibition, and probably a collection of phytochemicals are involved in this process. Conclusions: N. sativa is a good candidate for seeking the new anticholinesterase agent and could be considered as a good supplement for the health of the elderly.
Keywords: kinetic study